Association between chemokine CXC ligand 12 gene polymorphism (rs1746048) and coronary heart disease: A MOOSE-compliant meta-analysis. Issue 24 (June 2017) - Chen, Min; Jiang, Yu-Feng; Zhang, Nan-Nan; Yang, Hua-Jia; Xu, Lang-Biao; Rui, Qing; Sun, Si-Jia; Yao, Jia-Lu; Zhou, Ya-Feng
Abstract : Abstract: Recently a large number of investigations have implicated the association between the chemokine CXC ligand 12 gene polymorphism (rs1746048) and risk of coronary heart disease (CHD), but the results remain debatable. The aim of our study was to provide more compelling evidence for the relationship between rs1746048 and CHD risk. Studies eligible for this meta-analysis were identified through electronic search of PubMed, EMBASE, and CNKI. Two authors performed independent literature review and study quality assessment by using the Newcastle–Ottawa Scale checklist. The odds ratios (ORs) with 95% confidence intervals (CIs) were pooled in a specific genetic model to assess the association. The meta-analysis of 48, 852 patients and 64, 386 controls from 12 studies showed that patients with rs1746048 had 1.11 times of high risk in developing CHD (OR = 1.11; 95% CI = 1.09–1.14; P  < .005; I 2  = 35.8%). The increased risk of CHD was also found in both Asian (OR = 1.07; 95%CI = 1.02–1.12; P  < .005; I 2  = 40.6%) and Caucasian populations (OR = 1.14; 95% CI = 1.10–1.18; P  < .005; I 2  = 22.2%). The results of our meta-analysis suggested that chemokine CXC ligand 12 gene polymorphism (rs1746048) may be linked with susceptibility to CHD.